Increased Rates of Obstetric Complications Prior to Systemic Sclerosis Diagnosis. Issue 6 (22nd March 2022) - Chung, Melody P.; Kolstad, Kathleen D.; Dontsi, Makdine; Postlethwaite, Debbie; Manwani, Poonam; Zhao, Hongyu; Kesh, Sumana; Simard, Julia F.; Chung, Lorinda
Abstract : Objective: To investigate whether obstetric complications prior to systemic sclerosis (SSc) diagnosis are more common in SSc patients compared to the general obstetric population. Methods: A case–control study was performed at Kaiser Permanente Northern California to compare prior obstetric complications in adult women who later developed SSc (cases) with women from the general obstetric population who did not develop SSc (controls; matched 10:1 by age and year of delivery) from 2007 to 2016. Exposures included past hypertensive disorders of pregnancy (preeclampsia, eclampsia, gestational hypertension), premature rupture of membranes (PROM), intrauterine growth restriction (IUGR), maternal infections, neonatal intensive care unit (NICU) admission, and preterm birth. Fischer's exact tests were used to compare categorical variables. Conditional logistic regression models estimated the odds ratio (OR), and corresponding 95% confidence intervals (95% CIs) for the outcome SSc. Results: Seventeen SSc cases and 170 non‐SSc controls were identified, with median maternal age at delivery 34 years (range 23–46 years) and median time from delivery to SSc diagnosis 2 years (range 0.2–7.3 years). Women with SSc were more likely to be Hispanic and Black. Prior obstetric complications appeared higher in women with an eventual SSc diagnosis compared to controls (70.6% versus 50%), including hypertensive disorders (17.7% versus 9.4%), PROM (11.8% versus 4.1%), IUGR (5.9% versus 1.8%), maternal infection (29.4% versus 14.1%), NICU admissions (23.5% versus 7.7%), and preterm delivery (29.4% versus 21.8%). Women with SSc had a higher odds of delivering infants requiring NICU admission (OR 4.7 [95% CI 1.2–18.8]). Conclusion: Women who eventually develop SSc had trends toward more complicated pregnancy histories before overt diagnosis.